Penguatan Kesadaran Masyarakat dalam Menggunakan Produk Lokal sebagai Wujud Cinta Tanah Air - Asfan, Moch Faiz Kumara; Izzi, Alfi Liwaul; Fitrah, Aditya Guevara; Putera, Prama Daniswara Aqni; Muttaqien, Ardhian; Shabrina, Raissa Puan (LP2M Universitas Ibrahimy, 2026)
In the current era of globalization, the diversity of imported products presents challenges for Indonesian local products. Consumer choices are not only economic decisions but also reflect nationalism related to identity and economic sustainability. This study uses a qualitative descriptive method with a literature review of reputable journals from the past five years, discussing consumer preferences between local and imported products, brand image, digital marketing strategies for MSMEs, and the relationship between the use of local products and values of nationalism and cultural preservation. The collected data are analyzed to understand the supporting and inhibiting factors influencing young generations in choosing local products. The aim of this research is to identify and analyze the factors affecting the consumption behavior of young people toward local products, as well as to explore the role of culture and digital marketing in shaping their preferences. The results indicate that although young people are aware of nationalist values, in everyday practice, they do not fully prioritize nationalism as their main motivation in choosing products. Therefore, strengthening local product consumption needs to be pursued through education, product innovation, and effective digital marketing strategies as an expression of nationalism and sustainable economic independence.